2016
DOI: 10.1111/1753-6405.12552
|View full text |Cite
|
Sign up to set email alerts
|

Poor adherence to folic acid and iodine supplement recommendations in preconception and pregnancy: a cross‐sectional analysis

Abstract: Objective: To determine pregnant women's knowledge of and adherence to the recommendations for periconceptional folic acid supplementation (PFS) and iodine supplementation (IS). Secondary objectives include determining predictors of adherence, and identifying influential nutrition information sources. Methods:A cross-sectional online survey was completed by 857 pregnant women, including a national cohort (n=455) recruited using an online panel provider and a South Australian cohort (n=402) recruited from a pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
2
34
1
2
Order By: Relevance
“…A strength of the present study is the capture of ethnic background. In 2013, 75% of pregnant women in a country‐wide survey were born in Australia but only 48% reported their ethnic background as Australian . Thus ethnic background is likely to be more amenable to understanding cultural influences on iodine‐containing food practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strength of the present study is the capture of ethnic background. In 2013, 75% of pregnant women in a country‐wide survey were born in Australia but only 48% reported their ethnic background as Australian . Thus ethnic background is likely to be more amenable to understanding cultural influences on iodine‐containing food practices.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the re‐emergence of mild iodine deficiency in some states of Australia, two strategies were implemented to ensure that all segments of the population obtained sufficient iodine: in 2009, the addition of iodised salt to bread and, in 2010, pregnant and lactating women were advised to take a supplement containing 150 μg iodine per day because of their higher requirements . Studies conducted since 2010 indicate that reported use of iodine‐containing supplements in pregnancy is not universal, ranging from 66 to 81% in WA, Victoria, NSW and SA, with strict adherence to dose and regularity appearing to be lower . Therefore many pregnant women rely exclusively or partially on dietary intake to meet their iodine requirement, thus an understanding of the consumption patterns, changes in these patterns and knowledge of food sources of iodine during pregnancy is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women reported rarely discussing iodine with their HCP, and lacking knowledge of dietary sources and importance of iodine for fetal development (43) . In Australia, a country with mild iodine insufficiency in pregnancy and mandatory iodine fortification of salt and bread as well as recommendations for iodine supplementation in pregnancy, knowledge regarding the adverse outcomes of ID and the importance of iodine has been found to be consistently poor in pregnant women (52,(57)(58)(59)(60) . Low self-confidence on whether women met the iodine requirements (20 %) could be explained from the lack of knowledge of dietary sources of iodine.…”
Section: Women Of Childbearing Agementioning
confidence: 99%
“…Identifying the subtherapeutic potential of some products in the setting of an identified nutrient deficiency represents an important opportunity for intervention. The potential value of pharmacists contributing towards improved awareness around the use of supplements in pregnancy is further emphasised by a recent Australian study examining pregnant women's knowledge of and adherence to the recommendations for periconceptional folic acid and iodine supplementation . Although most women were aware of the importance of folic acid and iodine during pregnancy, only one in five women adequately adhered to the recommended intakes, even among those with planned pregnancies.…”
mentioning
confidence: 99%